2021
DOI: 10.1017/jfm.2021.343
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent inertial waves

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
2
1
0
Order By: Relevance
“…The scalings for are consistent with the findings from Nosan et al. (2021), where evanescent disturbances driven by forcing frequencies approximately equal to twice the mean rotation (i.e. ) were found to be ‘more or less independent of viscosity’ (i.e.…”
Section: Response To Low-amplitude Librationssupporting
confidence: 90%
See 1 more Smart Citation
“…The scalings for are consistent with the findings from Nosan et al. (2021), where evanescent disturbances driven by forcing frequencies approximately equal to twice the mean rotation (i.e. ) were found to be ‘more or less independent of viscosity’ (i.e.…”
Section: Response To Low-amplitude Librationssupporting
confidence: 90%
“…These quantities, α K and α E , provide approximate power-law scalings of the form K ∼ E α K and Ē ∼ E α E within the given range of Ekman numbers, [E, 10E], confirming the observations made above in the limit E → 0: for 0 < ω 0.29, Ē ∼ E −1 , whereas for ω 1 K is independent of E and Ē ∼ E −0.5 . The scalings for ω 1 are consistent with the findings from Nosan et al (2021), where evanescent disturbances driven by forcing frequencies approximately equal to twice the mean rotation (i.e. ω ≈ 1) were found to be 'more or less independent of viscosity' (i.e.…”
Section: Global Responsessupporting
confidence: 87%
“…For inertial waves, Nosan et al [37] have shown theoretically and experimentally how, in a rotating fluid, waves of frequency slightly larger than the Coriolis parameter f may propagate horizontally over large distances, limited only by viscosity, despite being vertically evanescent. They mentioned the same phenomenon in a stratified fluid, where internal waves of frequency slightly larger than the buoyancy frequency N are evanescent horizontally but may propagate vertically over large distances, limited only by viscosity.…”
Section: Internal Gravity Wavesmentioning
confidence: 99%